2016
DOI: 10.1016/j.ympev.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular data from contemporary and historical collections reveal a complex story of cryptic diversification in the Varanus (Polydaedalus) niloticus Species Group

Abstract: Previous studies of color pattern, tongue pigmentation, and scale counts have been used to distinguish two species of semiaquatic varanids in Africa, but these findings have yet to be tested with molecular data. The Varanus (Polydaedalus) niloticus Species Group is comprised of the Nile monitor (V. niloticus) and the Ornate monitor (V. ornatus). Due to the high rate of exploitation of both species for bushmeat, the leather industry, and the pet trade, a clear understanding of the taxonomy and genetic partition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 106 publications
(125 reference statements)
2
26
0
Order By: Relevance
“…Similar patterns and timing of diversification have been demonstrated in other vertebrate groups with non-forest distributions, including African clawed frogs (Furman et al, 2015), cobras (Trape et al, 2009), and lizards (Makokha et al, 2007; Diedericks and Daniels, 2014; Dowell et al, 2016), which have all been shown to form complexes of divergent populations correlated with the expansion of C 4 grasslands during the Miocene. Subsequent aridification in the Pliocene and Pleistocene likely explain the more recent cladogenic events in our analyses (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Similar patterns and timing of diversification have been demonstrated in other vertebrate groups with non-forest distributions, including African clawed frogs (Furman et al, 2015), cobras (Trape et al, 2009), and lizards (Makokha et al, 2007; Diedericks and Daniels, 2014; Dowell et al, 2016), which have all been shown to form complexes of divergent populations correlated with the expansion of C 4 grasslands during the Miocene. Subsequent aridification in the Pliocene and Pleistocene likely explain the more recent cladogenic events in our analyses (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Other studies with a larger geographic scope (that include Upper Guinea) have detected genetic breaks between populations in western Cameroon and those located in Nigeria, but west of the Niger River. The large sampling gap between the Niger and Cross Rivers in Nigeria leaves population boundaries unresolved, and whether these breaks coincide with the Cross River remains unknown (Dowell et al., ; Fuchs & Bowie, ; Fuchs, Fjeldså, & Bowie, ; Nicolas et al., , ). These patterns could also be the result of postulated sea incursions, which may have been the proximate cause of divergence (Penner, Wegmann, Hillers, Schmidt, & Rödel, ).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, widespread taxa including such high profile species as giraffe, lion, cheetah, and even elephant were managed primarily as panmictic populations throughout Africa. Over the past decade, however, molecular tools have uncovered deep divergence between West African and other lineages in these ( Bertola et al, 2015 ; Brown et al, 2007 ; Charruau et al, 2011 ; Dowell et al, 2015b ; Eaton et al, 2009 ; Shirley et al, 2014 ; Smolensky, Hurtado & Fitzgerald, 2014 ) and many other taxa, including the Nile crocodile ( Hekkala et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%